2022
DOI: 10.1002/sus2.70
|View full text |Cite
|
Sign up to set email alerts
|

Fe‐based catalysts for nitrogen reduction toward ammonia electrosynthesis under ambient conditions

Abstract: As one of the most important chemicals and carbon‐free energy carriers, ammonia (NH3) has significant energy‐related applications in industry and agriculture. Ninety percent of NH3 is produced by the Haber–Bosch process using high‐purity N2 and H2 at high temperatures and pressures, which consumes about 1% of the total energy production and causes 1.4% of global CO2 emissions. The environmentally friendly electrochemical nitrogen reduction reaction (NRR) with low energy consumption is a promising alternative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 135 publications
(265 reference statements)
0
40
0
Order By: Relevance
“…Thus, it is of essential significance to develop novel strategies to overcome the drawback of the aqueous electrolytes for their less gas solubility and larger proton concentrations. [ 92 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it is of essential significance to develop novel strategies to overcome the drawback of the aqueous electrolytes for their less gas solubility and larger proton concentrations. [ 92 ]…”
Section: Discussionmentioning
confidence: 99%
“…summarized recent advances and research progress in non‐noble Fe‐based catalysts applied in NRR and found that Fe‐based catalysts are excellent candidates for NH 3 synthesis, particularly for neutral electrolytes with lower potential. [ 92,93 ] Liu et al. reported a Fe single‐atom catalyst (SACs) for NRR and obtained a high FE of 18.6 ± 0.8% and NH 3 yield rate of 62.9 ± 2.7 µg h −1 mg −1 in neutral 0.1 m PBS electrolyte at room temperature and −0.4 V versus RHE.…”
Section: Aqueous Electrolytementioning
confidence: 99%
See 1 more Smart Citation
“…The approach may further provide a solution to design dual-metalsite catalysts for other critical electrocatalysis processes such as oxygen reduction to H 2 O 2 , 47 CO 2 reduction, 48 and nitrogen electrochemical reactions. 49,50 ■ ASSOCIATED CONTENT * sı Supporting Information…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated an effective strategy for a carbon catalyst doped with two atomic-scale transition metals (late transition metal Fe and early transition metal Zr) that exhibited improved performance and durability in an actual PEM fuel cell. The approach may further provide a solution to design dual-metal-site catalysts for other critical electrocatalysis processes such as oxygen reduction to H 2 O 2 , CO 2 reduction, and nitrogen electrochemical reactions. , …”
Section: Discussionmentioning
confidence: 99%